Neutralizing Antibody Response by Inactivated SARS-CoV-2 Vaccine on Healthcare Workers - Nataniel Tandirogang; Evi Fitriany; Nursaci Mardania; Miftahul Jannah; Bilqis Faiqotun Nabilah Dilan; Sapta Rahayuning Ratri; Arfian Deny Prakoso; Meiliati Aminyoto; Yuliana Kartika Ningrum; Ika Fikriah; Yadi Yadi (Molecular and Cellular Biomedical Sciences, 2023)
Background: Currently, the key to combat coronavirus disease 2019 (COVID-19) as a global pandemic is relying mainly on vaccination, and several factors might affect the level of protection. This study aimed to determine the quantitative increase of neutralizing antibody titer against COVID-19 and the influence of gender, body mass index (BMI), routine consumption of vitamin C, D, and E towards the neutralizing antibodies after vaccination.Materials and methods: One hundred nine health workers from various health facilities were recruited. Sinovac inactivated severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) vaccine was used in this study. Antibody titer measurements were carried out quantitatively using electrochemiluminescence immunoassay (ECLIA) on day 14 after the first and second doses administration of the vaccine.Results: The average of antibody titers after the first and second doses were 109.1 and 191.6 U/mL, respectively. Antibody titer significantly increased (p=0.000) as much as 82.5 U/mL from the first to the second dose. There was a significant difference in the increase in antibody titer between respondents who consumed vitamin E regularly and those who did not (p=0.036). Routine consumption of vitamin C and D, gender, and BMI did not affect the increase in neutralizing antibody titer with p-values of 0.983, 0.337, 0.186, and 0.424, respectively.Conclusion: Routine consumption of vitamin E is associated with post-SARS-CoV-2 vaccination neutralizing antibody response. Gender, BMI, and the routine consumption of vitamin C and D have no association with the immune response.Keywords: COVID-19, neutralizing antibody, inactivated SARS-CoV-2 vaccine